Positive effects of two decades of passive ecological restoration in a historically polluted marine site - Fanelli, Emanuela; Dell’Anno, Antonio; Nepote, Ettore; Martire, Marco Lo; Musco, Luigi; Bianchelli, Silvia; Gambi, Cristina; Falco, Pierpaolo; Memmola, Francesco; Coluccelli, Alessandro; Meola, Martina; Varrella, Stefano; et al. (Frontiers in Marine Science, 2023)
The Mediterranean Sea is one of the most exploited regions of the world's oceans. Here industrial activities have determined either acute or long-term impacts on coastal marine ecosystems. In this study, we investigated macrofauna distribution and diversity, and food-web functioning in a coastal area of the Mediterranean Sea facing an industrial chemical plant abandoned in the '90s to assess benthic ecosystem health. This area has been identified as a Site of National Interest (SNI) since 2002 and has been closed to any human activity awaiting to be remediated according to national laws. Our results indicate that, two decades after the SNI declaration (a decade after the plant decommissioning), there is no longer any sign of the impact of historical contaminations on macrofauna and benthic food web functioning. Overall, all the thirty-six sites showed high/good ecological quality according to the score assigned by AMBI and M-AMBI indexes, reflecting the absence of chronic impacts. Our findings reveal, for the first time, the positive effects of passive restoration (i.e., unassisted, or spontaneous recovery following cessation of anthropogenic impacts) on historically impacted coastal ecosystems since their health conditions, in terms of both abiotic (environmental variables and contaminant concentration) and biotic (macrofauna diversity and community composition, and benthic food-web structure) factors, were indistinguishable from surrounding non-impacted areas. These findings also suggest that other effective area-based conservation measures (OECMs) could be useful not only for biodiversity conservation of vulnerable and priority habitats in larger ocean sectors but also to promote the passive recovery of historically contaminated ecosystems.